2022
DOI: 10.1002/uog.24967
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional transvaginal ultrasound vs magnetic resonance imaging for preoperative staging of deep myometrial and cervical invasion in patients with endometrial cancer: systematic review and meta‐analysis

Abstract: What are the novel findings of this work?Our systematic review and meta-analysis comparing the diagnostic test accuracy (DTA) of three-dimensional transvaginal ultrasound (3D-TVS) and magnetic resonance imaging (MRI) for deep myometrial invasion (DMI) and cervical invasion demonstrated good performance of 3D-TVS, confirming its value for preoperative staging and surgery planning in patients with endometrial cancer. What are the clinical implications of this work?This is the first systematic review to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Some recent studies focusing of low risk histology cases have shown that TVS and MRI have similar diagnostic performance for identifying myometrial infiltration in such cases. [6][7][8] The results of this study should prompt new research. In modern Gynecologic Oncology, sentinel lymph node biopsy (SLNB) in endometrial cancer has become a standard of care in many institutions.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Some recent studies focusing of low risk histology cases have shown that TVS and MRI have similar diagnostic performance for identifying myometrial infiltration in such cases. [6][7][8] The results of this study should prompt new research. In modern Gynecologic Oncology, sentinel lymph node biopsy (SLNB) in endometrial cancer has become a standard of care in many institutions.…”
mentioning
confidence: 78%
“…This fact might bias the results and could overestimate the actual diagnostic accuracy of both TVS and MRI in low‐risk cases, where preoperative assessment of myometrial and cervical invasion makes sense from the point of view of the gynecologic oncologist. Some recent studies focusing of low risk histology cases have shown that TVS and MRI have similar diagnostic performance for identifying myometrial infiltration in such cases 6–8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative analysis and surgical planning are essential before surgical lymphadenectomy. The meta-analysis discovered that 3D-transvaginal ultrasound and magnetic resonance imaging (MRI) have good diagnostic accuracy in detecting preoperative staging and surgical planning of endometrial cancer patients [ 12 ]. Positron emission tomography-computed tomography (PET-CT) has also been proven to have excellent preoperative staging and lymph node metastasis diagnostic performance [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the identification of women with hyperplasia and atypia is of paramount importance to reduce the burden of endometrial cancer. The identification of women suffering with abnormal uterine bleeding, and with those with abnormal endometrial thickness (evaluated by trans vaginal ultrasound (TVS)) [ 17 ] is making screening and early diagnosis possible, even in endometrial cancer patients [ 18 ]. Finding a screening test for endometrial cancer is challenging, but early detection is more and more possible.…”
mentioning
confidence: 99%